Factors Influencing the Willingness to Pay for Wetland Bird Protection: A Value Assessment Based on a Questionnaire Survey of Residents in Gahai Wetland, Gansu, China - Xiushan Li; Xiaoliang Shi; Tiantian Yu; Jinhong Du; Tom D. Breeze (Animals)
The Gahai wetland in Gansu, China, is a key wetland for nationally and globally threatened bird species. This research aims to quantify the economic value of wetland birds by the method of contingent valuation questionnaire, thereby providing a foundation for conservation of avian species. The result indicated that residents were willing to pay between 208 and 230 CNY (29–32 USD $) annually for bird protection, a total annual value of wetland birds in Luqu County ranging from 7.9 M to 8.8 M CNY (1.1–1.3 M USD $). Men, locals, and older individuals were more inclined to contribute and offered higher payments, albeit non-significant correlation between education level and annual income with the willingness to pay. While the depth of understanding of wetland pressures did not significantly influence the willingness to pay, it did show a positive correlation; those with more profound understanding tended to be more generous in their payments. Tibetan male residents were more likely to prioritize ecological and environmental protection due to their religious beliefs and cultural customs, which emphasize the reverence for and compassion towards birds. This research not only complemented and validated the applicability of the contingent valuation method in China but also underscores the considerations that should be taken into account when employing this method.